Control in bioprocessing : modeling, estimation and the use of soft sensors - López Pérez, Pablo Antonio, 1981-; Lopez, Ricardo Aguilar, 1964-; Femat Flores, Alejandro Ricardo (John Wiley & Sons, Inc., 2020)
"This chapter aims to develop in some detail the bases and concepts of bioprocesses related to the control theory introduced in basic principles of mathematical modeling in bioprocesses. From this viewpoint, the systems approach to bioengineering and bioprocessing, with its current focus on the development of mathematical models and their analysis, is a logical sequel that the control theory will play a relevant role in understanding the mechanisms of cellular and metabolic processes. It concerns specifically applications in modeling, estimation, and control of bioprocesses. Consequently, there are many exciting opportunities for control experts who want to shift their interests to bioprocesses"-- Provided by publisher.
Keywords: Biochemical engineering.; Process control.; elektronické knihy; electronic books